Metabolic Disease in Subadult Skeletal Remains from Late Ottoman-Era Tell Hisban, Jordan - Edwards, Emily Arlene (East Carolina University, 2019)
The site of Tell Hisban in Jordan was seasonally occupied by nomadic agropastoral tribes for over a thousand years. In the latter half of the 1800s, the Ottoman Empire instituted the Tanzimat, a series of reforms intended to solidify control over the region, including a new system of private land ownership. This new land law conflicted with traditional tribal-based land rights and resulted in intensification of agricultural production and diminished pastoralism in the regional economy. During this period of economic change, at least 62 individuals were interred in ruins on Tell Hisban, of which 55% were non-adults. Many long bones and cranial elements of non-adults within these commingled remains display evidence of vitamin C (scurvy) and D (rickets) deficiencies at a greater frequency than pre-Tanzimat or earlier regional cemeteries. Increased agricultural production may have impacted the availability of traditional foods high in ascorbic acid that prevented scurvy in past groups, and increased reliance on cereals, which lack key macronutrients. The resulting shift in diet would have disproportionately affected individuals more susceptible to nutritional stressors, such as pregnant women, infants, and weaning children. In the case of rickets, these nutritional stressors may have been exacerbated by cultural barriers which limited an individual's exposure to sunlight and may have resulted in the surprising presence of rickets in this high-ambient UV radiation environment. Together with genetic predispositions to scurvy or rickets, these biocultural changes likely contributed to increased frailty in the form of metabolic disease for infants and young children within this population compared to earlier groups at Tell Hisban and contemporary populations in other areas of Jordan and Israel.
Keywords: Scurvy; Rickets; vitamin C deficiency; vitamin D deficiency; Tell Hisban; Tell Hesban; bedouin; health; osteology; nutrition; Human remains (Archaeology)-- Jordan--19th century; Bones--Metabolism--Disorders--Jordan--19th century; Children--Diseases--Jordan--19th century; Jordan--Social conditions--19th century